Analysis of Leadership Influence Factors on Company Management Success - Suryawan, Teguh; Mubarok , Husni (Universitas Sains dan Teknologi Komputer, 2024)
Companies are legal entities that play an important role in the national economy. Like a human body, a company also needs good organization to achieve the targets and goals of the company. Company failures resulting from poor company management occur in international companies, namely the company Apple Inc, which is the most valuable company in the world which ends in 2022, reminding the importance of leadership in company. The research method used in this research uses the Systematic Literature Review method. There are several types of leadership in companies, including four, namely democratic, autocratic, affiliative and visionary leadership. This study concludes that leadership factors in operational management, finance and public relations have a significant impact on companies. Companies that implement democratic leadership tend to be more able to carry out management in all sectors of the company, while companies that implement leadership based on Islamic studies make the relationship between leaders and subordinates more peaceful compared to other types of leadership.